ANALYSIS OF THE RELATIONSHIP BETWEEN HIV/AIDS KNOWLEDGE AND STIGMA AGAINST PEOPLE LIVING WITH HIV/AIDS (PLWHA) IN WOMEN OF CHILDBEARING AGE (WUS) IN INDONESIA (ADVANCED ANALYSIS OF THE 2017 IDHS) - Putri Pulungan, Indah Rizky; Arlianti, Nopa; Abdullah, Asnawi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: HIV is a disease that can attack the body’s immune system. Knowledge of HIV/AIDS influences stigma towards people living with HIV/AIDS (PLWHA). Therefore, there is a misunderstanding regarding the transmission process of HIV/AIDS, such as shaking hands and eating together, which causes stigmatization of PLWHA. To date, the world/s cases have reached around 38 million. HIV/AIDS cases in Indonesia currently reached 537.730. The purpose of this study was to find out how much knowledge is related to stigma towards PLWHA among Women Childbearing Age (WUS) in Indonesia (Advanced Analysis of the 2017 IDHS). Method: This research used the descriptive-analytic method with cross-sectional design. The population in this study were all WUS aged 15–49 years. The samples in the study were 7.286 respondents. Data collection was carried out using secondary raw data IDHS 2017. Data analysis used the Chi square test and logistic regression with STATA computer program. Results: The result showed that the level of knowledge was good (41.81%) and the level of knowledge was poor (50.98%), while the level of knowledge was sufficient (57.14%). The results of the chi- square test showed that the P-value=0.000, which means that there is a relationship between knowledge and stigma towards people living with HIV/AIDS. Multivariate test showed that knowledge, age of WUS, Parity, and area of residence were the variables most related to stigma towards PLWHA. Recommendation: It is hoped that the Ministry of Health of the Republic of Indonesia can develop various programs to increase public knowledge about HIV/AIDS.